The conceptual development of slight cognitive impairment as a diagnostic category: A historical perspective. - Cammisuli, Davide Maria; Sportiello, Marco Timpano; Guazzelli, Mario (Rivista di Psicologia Clinica, 2013)
Historically, many attempts have been made to classify the boundary state between physiological and pathological aging. After Kral (1962), who distinguished a physiological cognitive decline from a pathological one, the conceptual turnover was the classification of Mild Cognitive Impairment (MCI) by Petersen et al. in 1995. It represents the most important nosological entity currently adopted by clinicians to diagnose the preclinical phase of Alzheimer’s Disease. However, clinical research on slight cognitive impairment did not provide inclusion/exclusion criteria and exact psychometric norms for such a diagnosis. In order to clarify the debate on the topic, we have given a comprehensive historical review of conceptual and nosographic aspects of all clinical entities which report a slight cognitive impairment, pointing out their neuropsychological features. As a result, we suggest a new categorization of slight cognitive impairment clinical entities, and we discuss some aspects of MCI evaluation that remain still unclear, in the light of recent revision of diagnostic criteria and psychiatric classification.